(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The teacher integrative characteristics as the English Language education process managers are thought to be the whole unity of their professional activity psychological, pedagogical and subject components, necessary for the integration process implementation on the level of English Language various subject links.